Malaria in Pregnancy : A Qualitative Study on Health Belief Model in Muara Wahau East Kalimantan - Ike Anggraeni Gunawan; Annisa Nurrachmawati (Jurnal Kesehatan Masyarakat Andalas, 2017)
Pregnant women who infected by malaria were three times more likely to suffer from other diseases. This study aimed to explore Kutai cultural perspectives, behaviors, perceived susceptibility, perceived severity, perceived benefits and barriers, perceived threat and cues to action associated with malaria in pregnancy. The qualitative study was conducted through indepth interviews of 37 informants consist of maternal, their husbands, health workers and local community leaders. This study revealed that malaria was not a threat because of the perception that malaria only exposed in forest. The community already had good health seeking behavior. All informants knew that malaria as a dangerous disease especially during pregnancy but no one knew malaria in pregnancy can cause anemia, low birth weight, miscarriage and stillbirth. At the individual level, almost all informants have taken preventive health behavior using mosquito nets, mosquito electric, repellent lotion, and burning dried leaves. At the community level prevention activities called gotong royong (all members of community work together) to keep the environment clean to reduce the mosquito breeding place was rarely done.